Reliability analysis and evaluation of automotive seat angle-adjuster. Issue 3 (1st September 2020) - Liu, Xintian; Liu, Lei; Wu, Que; Yuan, Xinjie; Huang, Hu
ABSTRACT: The reliability of automobile seat angle-adjuster directly affects the safety of automobiles. In order to improve the reliability of automobile seat angle-adjuster, the structure of seat angle-adjuster is optimised by bench test. The bench test of seat angle-adjuster is carried out in the light of the standard of enterprise and the seat angle-adjuster structure is improved based on the experimental results. The finite-element model of seat angle-adjuster is established according to parameters of seat angle-adjuster and the finite-element analysis is presented under the boundary conditions. The validity of finite-element model of seat angle-adjuster is verified by comparing the results of bench test with finite-element analysis. The reliability model of seat angle-adjuster system is established on the basis of relationship of key components. The reliability analysis of seat angle-adjuster is put forward based on stress strength interference model and competing risk theory. These results provide a technical support for the promotion of automobile seat angle-adjuster.